Production method and varietal source influence the volatile profiles of spirits prepared from fig fruits (Ficus carica L.) - Rodríguez-Solana, Raquel; Galego, Ludovina R.; Peréz-Santín, Efren; Peréz-Santín, Efren; Romano, Anabela (European Food Research and Technology, 2019)
Fig fruits (Ficus carica L.) are used in several Mediterranean countries to produce alcoholic spirits, with either plurivarietal dried figs or, monovarietal fresh figs as the raw material. To determine the influence of different varietal attributes and production methods on the quality of fig spirits, we analyzed the volatile compounds that contribute to the aroma and organoleptic characteristics of spirits derived from eight Portuguese varieties of fresh figs, as well as mixtures of dried figs processed in the laboratory and plurivarietal fig spirits already in the market. The quantification of major and minor volatiles by GC-FID revealed that the plurivarietal dried fig spirits contained greater quantities of short-chain fatty acid esters and higher alcohols (associated with poor-quality spirits) and compounds with a negative influence on aroma and flavor (such as ethyl lactate, ethyl acetate and diethyl succinate) than the fresh fig spirits. HS-SPME/GC-MS analysis detected 130 volatile compounds, among which the esters ethyl decanoate, ethyl octanoate and ethyl dodecanoate, the aldehydes benzaldehyde and furfural, the monoterpene limonene and the norisoprenoide beta-damascenone were common constituents in most of the spirits. The volatile profile of all dried fig distillates was similar and diverse, reflecting the plurivarietal origin, whereas the monovarietal fresh fig spirits produced distinct profiles (sufficient for varietal chemical differentiation), with Burjassote branco distillates containing the greatest number of volatile compounds. This volatile analysis provides a way to determine the quality of fig spirits objectively and to develop spirits with novel characteristics for the market.
Keywords: fruit spirits; monovarietal; HS-SPME; volatile compounds; figs; JCR; Scopus